Smallholder farmer cropping decisions related to climate variability across multiple regions - Wood, SA; Jina, AS; Jain, M; Kristjanson, Patricia M.; DeFries, Ruth S. (Elsevier, 2014)
A long history of household-level research has provided important local-level insights into climate adaptation strategies in the agricultural sector. It remains unclear to what extent these strategies are generalizable or vary across regions. In this study we ask about three potential key factors influencing farming households’ ability to adapt: access to weather information, household and agricultural production-related assets, and participation in local social institutions. We use a 12-country data set from sub-Saharan Africa and South Asia to explore the links between these three potential drivers of agricultural change and the likelihood that farmers made farm-associated changes, such as adopting improved crop varieties, increasing fertilizer use, investing in improved land management practices, and changing the timing of agricultural activities. We find evidence that access to weather information, assets, and participation in social institutions are associated with households that have reported making farming changes in recent years, although these results vary across countries and types of practices.